Current Status of Immune Deficiency Pathway in Tenebrio molitor Innate Immunity - Jang, Ho Am; Kojour, Maryam Ali Mohammadie; Patnaik, Bharat Bhusan; Han, Yeon Soo; Jo, Yong Hun (Frontiers in Immunology, 2022)
Yellow mealworm (Tenebrio molitor) is a highly beneficial beetle that serves as an excellent source of edible protein as well as a practical study model. Therefore, studying its immune system is important. Like in other insects, the innate immune response effected through antimicrobial peptides production provides the most critical defense armory in T. molitor. Immune deficiency (Imd) signaling is one of the major pathways involved in the humoral innate immune response in this beetle. However, the nature of the molecules involved in the signaling cascade of the Imd pathway, from recognition to the production of final effectors, and their mechanism of action are yet to be elucidated in T. molitor model. In this review, we present a general overview of the current literature available on the Imd signaling pathway and its identified interaction partners in T. molitor.